2022
DOI: 10.1038/s41598-022-08978-4
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic benefits of methionine restriction in adult mice do not require functional methionine sulfoxide reductase A (MsrA)

Abstract: Methionine restriction (MR) extends lifespan and improves several markers of health in rodents. However, the proximate mechanisms of MR on these physiological benefits have not been fully elucidated. The essential amino acid methionine plays numerous biological roles and limiting its availability in the diet directly modulates methionine metabolism. There is growing evidence that redox regulation of methionine has regulatory control on some aspects of cellular function but interactions with MR remain largely u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 57 publications
1
8
0
Order By: Relevance
“…Interestingly, dimethyl sulfide (DMS) is reported to extend lifespan in C. elegans and in Drosophila in an MsrA -dependent manner 67 . In contrast, MsrA was reported to be nonessential for metabolic benefit of MetR in mice 68 . Whether MsrA is required for lifespan extension in other contexts in various organisms including mammals needs to be tested in the future.…”
Section: Discussionmentioning
confidence: 95%
“…Interestingly, dimethyl sulfide (DMS) is reported to extend lifespan in C. elegans and in Drosophila in an MsrA -dependent manner 67 . In contrast, MsrA was reported to be nonessential for metabolic benefit of MetR in mice 68 . Whether MsrA is required for lifespan extension in other contexts in various organisms including mammals needs to be tested in the future.…”
Section: Discussionmentioning
confidence: 95%
“…Previously we showed that MsrA was not required to mediate the beneficial physiological effects of MR on glucose metabolism and body weight/composition. In these studies, we found that the lack of MsrA in mice manifested greater loss in lean and fat mass with MR, as well as larger improvements to glucose metabolism relative to normal diet compared to that in control mice 19 . These results suggest MsrA has an uncharacterized role in mediating or modulating MR.…”
Section: Introductionmentioning
confidence: 80%
“…We have described all husbandry conditions, the genetic mutant MsrA KO mouse, and diets used in this study in our previous publications 19 , 20 , 39 . All mice were maintained in the C57Bl/6J background and MR diets used were control diet (CD) (0.86% Met, TestDiet 578F w/0.86% MET – 5SFD) or MR (0.15% Met, 0% Cys, Test Diet 96D2, modified TestDiet 58B0).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations